Athlete burnout: What we know, what we could know, and how we can find out more - Eklund, R. C.; DeFreese, J. D. (International Journal of Applied Sports Sciences, 2015)
Although many, likely most, athletes will not experience burnout in any meaningful degree in their sport endeavors, it can be an important concern for the psychological health and well-being of some athletes choosing to invest intensely in highly demanding competitive sport environments. This aversive chronic experiential state is of interest to clinicians and researchers alike because of its impact on athletes experiencing its characterizing symptoms. The phenomenon of burnout has been discussed and investigated in broader professional environments since the early 1970s (Freudenberg, 1974), but has only been a construct of interest among sport scientists, professionals and participants for about the last 25-30 years (see Smith, 1986; Dale & Weinberg, 1990 for early discussions of athlete burnout). After approximately a quarter century of examination, it is appropriate to take stock of the accumulated research on the athlete burnout construct at large. The purpose of the current review is threefold in nature. We start by remembering the important, groundbreaking athlete burnout research of the past but, guided by the prose of Walt Whitman, move on to outline potential future directions as "much unseen" remains relative to the understanding, conceptualization, and intervention/prevention of athlete burnout. Finally, we consider suggestions for how to unearth future burnout knowledge and/or implement the potential interventions outlined herein. So, while important conceptualizations and empirical studies in the area are reviewed, much of this information is delimited by reference to already available excellent reviews of athlete burnout research; although, some research immerging in the interim is also considered. Our goal is to take stock of the conceptual understanding and extant research on athlete burnout and to spark future research and practice as described herein by other researchers and clinicians. An endeavor of that sort inherently requires provision of some initial commentary on the construct and its development.